Numerical Analysis on Effects of Soil Improvement on Pile Forces on Existing High-Rise Building - Thanapon Tipsunavee; Goran Arangjelovski; Pornkasem Jongpradist (Buildings, 2023)
Nowadays, seismic codes are regularly updated with new knowledge and a better understanding of the earthquake phenomenon. With these updates, existing buildings require a reevaluation of their stability and a process of reinforcement and/or retrofitting. This study investigated the effects of two types of ground improvement which use cement-mixing soil surrounding the foundation structure to reduce and redistribute forces acting on piles. This is especially important when the reevaluation of high-rise buildings leads to increased forces in the piles. Typically, buildings are designed while assuming fixed base boundary conditions at the foundation level, without considering soil–pile–structure interaction (SPSI). SPSI significantly influences the response of high-rise buildings supported by soft soil. Increasing the lateral resistance of the surrounding soil can reduce the influence of SPSI. In this study, a detailed dynamic numerical analysis was used to investigate the dynamic response of an SPSI system of a high-rise building under seismic load. A dynamic analysis was conducted on a modified layout of a real building, using real-time earthquake motion. The finite element program DIANA FEA was used to perform nonlinear 3D FEM numerical simulations, taking into account the essential SPSI phenomena, gap-slip between the piles and the soil, and free-field boundary conditions. A comparison of the data suggests that the bending moment and shear forces in the piles are reduced in magnitude and evenly distributed along the upper part of the pile, which reduces the stress concentration of the bending moment and shear forces at the contact between the piles and the pile cap.